Bombast Bombardment and Dense Syntax versus Effective Communication and Language Teaching in ESL Settings : Nigerian English Examples - Ekundayo, Omowumi Olabode Steven (Colombian Applied Linguistics Journal, 2021)
Influenced by certain factors and motives, some educated Nigerian English speakers use high-sounding expressions, as well as dense, windy, and complex syntactic structures. This paper examines this linguistic habit in Nigerian English to show how entrenched it has become; explain the sociolinguistic, historical, and idiosyncratic factors that influence it; show its effect on its audience and readers; and determine its implications for teaching and learning English in English as a second language (ESL) settings. The paper adopted the qualitative research method, and data were extracted from both primary and secondary sources. Primary data were extracted from well-known Nigerian ‘bombast bombardiers’ (users of bombast). Secondary data were gleaned from historical events and published and creative works. The study established that the use of ‘language explosives’ (high-sounding lexical items) is a common linguistic habit in ESL. Some educated Nigerians, for instance, use the habit to show off learning and their mastery of the language, estrange others in communication, create humor, and gain popularity. Although the paper avers that the habit in its unguided form hampers effective communication, it submits that it possesses certain socio-political and pedagogical utilities in ESL settings.